Establishment and verification of reference intervals for blood cell analysis in extremely high altitude - Yuan, Zhimin; Zhuang, Jian (Frontiers in Physiology, 2024)
Objective Establishment of reference intervals for complete blood count (CBC) in healthy adults at very high altitudes. Methods This study recruited 4,863 healthy adults who received routine health check-ups at Ali District People's Hospital from January 2019 to December 2021 through the LIS system. CBC was detected by XT-4000i automatic cell analyzer and statistically analysed by SPSS 23.0 software. In addition, 20 health check samples were collected in 2022 to validate the established reference intervals. Results The CBC count showed a non-normal distribution in each item separately. The white blood cell (WBC), neutrophil (NEUT), lymphocyte (LYMPH), monocyte (MONO), eosinophil (EO), basophil (BASO), red blood cell (RBC), hemoglobin (HGB), hematocrit (HCT), mean corpuscular volume (MCV), mean hemoglobin content (MCH) and mean erythrocyte hemoglobin concentration (MCHC) levels of healthy adults were significantly different from the national clinical reference range (p < 0.05). There were significant differences between male and female in RBC, HGB and HCT levels (p < 0.05). The new reference intervals were less consistent with the expert consensus CBC reference intervals (p < 0.05). Compared with the other reference intervals, the diagnostic value of the reference screening interval established was significantly higher in this study (p < 0.05). The reference range established is verified by 20 independent samples from 2022, and the results are acceptable. Conclusion This study preliminarily established reference intervals for CBC of healthy adults in the Ali region of Tibet, to provide a reference point for understanding routine blood markers in permanent residents of high-altitude environments.